An adaptable direct simulation Monte Carlo method for simulating acoustic agglomeration of solid particles. (15th February 2022) - Wu, Zhihao; Fan, Fengxian; Yan, Jinpei; Chen, Houtao; Hu, Xiaohong; Su, Mingxu
Graphical abstract: Highlights: An adaptable direct simulation Monte Carlo method was developed. Coexistence of agglomeration and rebound as collision consequences was modelled. Simulations of acoustic agglomeration were validated against experimental results. Evolution of acoustic agglomeration behaviors with time was demonstrated. Influence of restitution coefficient on acoustic agglomeration was examined. Abstract: An adaptable direct simulation Monte Carlo (DSMC) method that settles the challenge of coexistence of agglomeration and rebound as a consequence of inter-particle collisions was developed to simulate acoustic agglomeration of solid particles. The method was validated against experimental data under a range of operational conditions. Based on this, the evolution of particle size distribution, agglomeration efficiency and agglomeration behavior with time was numerically investigated. The effect of restitution coefficient on the performance of acoustic agglomeration was also examined. The results show that the occurrence of acoustic agglomeration yields a significant decrease in the number concentration of small particles and a small increase in the number concentration of large particles. Moreover, a worse performance of acoustic agglomeration at a higher restitution coefficient is observed. This study demonstrated the power of the proposed method in simulating the acoustic agglomeration and provided a fundamental approach for investigating the dispersed gas-solid two-phase flows.